Improving the Robustness of Electromyogram-Pattern Recognition for Prosthetic Control by a Postprocessing Strategy - Zhang, Xu; Li, Xiangxin; Samuel, Oluwarotimi Williams; Huang, Zhen; Fang, Peng; Li, Guanglin (Frontiers in Neurorobotics, 2017)
Electromyogram (EMG) contains rich information for motion decoding. As one of its major applications, EMG-pattern recognition (PR) based control of prostheses has been proposed and investigated in the field of rehabilitation robotics for decades. These prostheses can offer a higher level of dexterity compared to the commercially available ones. However, limited progress has been made towards clinical application of EMG-PR based prostheses, due to their unsatisfactory robustness against various interferences during daily use. These interferences may lead to misclassifications of motion intentions, which damage the control performance of EMG-PR based prostheses. A number of studies have applied methods that undergo a post-processing stage to determine the current motion outputs, based on previous outputs or other information, which have proved effective in reducing erroneous outputs. In this study, we proposed a post-processing strategy which locks the outputs during the constant contraction to block out occasional misclassifications, upon detecting the motion onset using a threshold. The strategy was investigated using three different motion onset detectors, namely mean absolute value (MAV), Teager-Kaiser energy operator (TKE), or mechanomyogram (MMG). Our results indicate that the proposed strategy could suppress erroneous outputs, during rest and constant contractions in particular. In addition, with MMG as the motion onset detector, the strategy was found to produce the most significant improvement in the performance, reducing the total errors up to around 50% (from 22.9% to 11.5%) in comparison to the original classification output in the online test, and it is the most robust against threshold value changes. We speculate that motion onset detectors that are both smooth and responsive would further enhance the efficacy of the proposed post-processing strategy, which would facilitate the clinical application of EMG-PR based prosthetic control.